The sense of agency in autism spectrum disorders: a dissociation between prospective and retrospective mechanisms? - Zalla, Tiziana; Sperduti, Marco (Frontiers in Psychology, 2015)
While a large number of studies have reported impairments in social and interpersonal abilities in individuals with autism spectrum disorder (ASD), relatively few studies have focused on self-related knowledge in this population. One of the processes implicated in the physical dimension of the Self is the sense of agency (SoA), i.e., the experience of initiating and controlling one’s own actions and producing desired changes in the world via these actions. So far, the few studies investigating SoA in ASD have reported contrasting results, with some showing spared, others impaired SoA. Here, we review the existing literature and suggest that the distinction between prospective and retrospective mechanisms of the SoA might help reconcile the existing findings. In the light of a multi-componential model of SoA, we propose the view that a specific impairment at the level of prospective mechanisms acting on internal agency signals (i.e., the intention, action selection, or command produced to achieve the goal) may be responsible for the reduced SoA in ASD, along with spared retrospective mechanisms. Future research should shed light on the impact of abnormal SoA on social and self-related dysfunctions in ASD.